MEMPERKASAKAN SISTEM TERAS PERBANKAN ISLAM DENGAN KONTRAK SYARIAH, BLOK RANTAI DAN KONTRAK PINTAR: SUATU KAJIAN KUALITATIF : Empowering Islamic Core Banking System with Shariah Contract, Blockchain and Smart Contract: A Qualitative Study - Mohd Tarmizi, Mohd Naufal; Buang, Ahmad Hidayat; Daud, Mohd Zaidi (Jurnal Syariah, 2023)
Nowadays Islamic core banking system is developed based on an open architecture that allows the integration of multiple systems and modules that ease the functionality to be added, replaced, and amended. Though it becomes easier, however, the Islamic core banking system is exposed to Shariah risk as simple as a change request that can affect a parameter which is Shariah compliance may become non-compliance due to changes in a single line of coding. Thus, this article evaluates the prospect of integrating Shariah requirements in the core banking system by virtue of Shariah compliance principles under the Islamic Financial Services Act 2013 aside from evaluating the prospect of empowering the functionality of the core banking system by referring to previous studies on blockchain and smart contract technologies. A qualitative approach via textual study, legal doctrine, and interviews was undertaken in this study to analyze data related to Shariah contract requirements, blockchain and smart contract. This article found that financial technologies such as blockchain and smart contract if integrated into the Shariah contract-based core banking system can mitigate counterparty risk, provide high-quality data, elevate the integrity of Shariah compliance processes, protect the transparency of data and processes, and act as an enforcement tool for contract conclusion.